PERLINDUNGAN HUKUM TERHADAP PEKEBUN SAWIT SWADAYA DALAM PENERAPAN HARGA TANDAN BUAH SEGAR (TBS) DI KECAMATAN TUALANG, KABUPATEN SIAK, RIAU - Harni Lisa Fitri; Maryati Bachtiar; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The independent palm orchard is one of the manufacturers in theproduction of palm oil other the plasma gardener and palm company in Tualangoxford, Siak municipality, Riau, the independent palm farmers have helpedcoountries to improve economic development in Indonesia but in the case, theindependent palm farmer did not properly receive the price of fresh fruit 11% to48% of the price hikes cut by palm oil producer have caused the independentpalm farmers to suffer losses in palm production activities, this results in adecline in the production due to the lack of the ability of the independent palmorchard to care for and plant cultivation, the independent palm orchard thing isthiking steps to increase the coprative production of palm oil rather than quality,by expending the land of palm plantations, which of course can have a negativeimpact on the environment in Tualang oxford, Siak municipality, Riau.As for the problem that the writer is making the basis of I this study, howdoes the price of fresh palm fruit go to the independent palm orchard in Tualangoxford, Siak municipality, Riau, and are independent palm gardens in Tualangoxford, Siak municipality, Riau obtaining protection in the sale of fresh fruitplants under Indonesia’s minister of agriculture no. 01/PERMENTAN/KB.120/1/2018 regarding guidelines for the purchase of fresh crop and fresh fruit from thefarmers’ production palm, and 2020 governor Riau rules No.77 of the policy ofpurchasing fresh fruit from palm oil production in the province of Riau.The kind of study used by the author is a sociological law study, alsoreferred to as the study of doctrinal law, from this sociological study of law theauthors conducted the study using the systemic criteria of the law, plants underIndonesia’s minister of agriculture no. 01/PERMENTAN/KB.120/1/2018regarding guidelines for the purchase of fresh crop and fresh fruit from thefarmers’ production palm article 2 mentions that the ministry’s rule is to provideprotection to the gardeners in obtaining fair prices of fresh fruit and avoidingunhealthy competition between plantatin companies, chapter 10 verse (10) cand2020 governor Riau rules No.77 of the policy of purchasing fresh fruit from palmoil production in the province of Riau.Keywords: Palm, Independent gardeners, TBS